Clinical advantages and neuroprotective effects of monitor guided fang’s capillary fascia preservation right RLN dissection technique - Shi, Qian; Xu, Jiaqi; Fang, Jugao; Zhong, Qi; Chen, Xiao; Hou, Lizhen; Ma, Hongzhi; Feng, Lin; He, Shizhi; Lian, Meng; Wang, Ru (Frontiers in Endocrinology, 2022)
Objective: To investigate the feasibility and advantages of Fang’s capillary fascia preservation right recurrent laryngeal nerve (RLN) dissection technique (F-R-RLN dissection) with preservation of the capillary network and fascia between the RLN and common carotid artery for greater neuroprotective efficiency compared with traditional techniques. Methods: We retrospectively analyzed 102 patients with papillary thyroid carcinoma undergoing right level VI lymph node dissection in our department from March 2021 to January 2022. Sixty patients underwent F-R-RLN dissection (the experimental group) and 42 patients underwent standard dissection (the control group). The intraoperative electrical signal amplitude ratios of the RLN, the number of dissected lymph nodes, and preservation rate of the parathyroid glands were recorded and compared between the two groups. Results: The electrical signal amplitude ratio of the lower neck part point of the RLN to the upper laryngeal inlet point in the experimental group was significantly lower than the ratio in the control group (p = 0.006, Z-score = -2.726). One patient suffered transient RLN paralysis in both groups, but this resolved within 1 month postoperative. There were no significant differences between the two groups in terms of the number of level VIa and level VIb lymph nodes dissected, nor in the rate of preservation of the parathyroid glands. Conclusions: F-R-RLN dissection is a thorough dissection technique that is effective at preventing an electrical signal amplitude decrease in the RLN, and at preventing RLN paralysis by preserving its blood supply.